2022
DOI: 10.7717/peerj.13111
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of digital mental health interventions for university students: an umbrella review

Abstract: Background Poor mental health among university students remains a pressing public health issue. Over the past few years, digital health interventions have been developed and considered promising in increasing psychological wellbeing among university students. Therefore, this umbrella review aims to synthesize evidence on digital health interventions targeting university students and to evaluate their effectiveness. Methods A systematic literature search was performed in April 2021 searching PubMed, Psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Awareness around recognizing and managing cognitive health concerns is comparatively lacking, and implicates a need for further promotion, particularly in vulnerable subgroups such as students. Pandemic control measures such as physical distancing and social isolation have only further emphasized the utility of digital technology-based tools and interventions for health and wellbeing among the general population, in addition to specific cohorts such as university students ( Harith et al, 2022 ), individuals with dementia ( Bird and Lim, 2022 ), and rural, regional, and remote communities ( O’Kane, 2020 ). Such resources (e.g., audio-visual telehealth platforms, smartphone applications, web-based forums or groups) are useful in connecting individuals to information, self-help strategies, health professionals, or peers, during periods of lockdown or restricted access.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness around recognizing and managing cognitive health concerns is comparatively lacking, and implicates a need for further promotion, particularly in vulnerable subgroups such as students. Pandemic control measures such as physical distancing and social isolation have only further emphasized the utility of digital technology-based tools and interventions for health and wellbeing among the general population, in addition to specific cohorts such as university students ( Harith et al, 2022 ), individuals with dementia ( Bird and Lim, 2022 ), and rural, regional, and remote communities ( O’Kane, 2020 ). Such resources (e.g., audio-visual telehealth platforms, smartphone applications, web-based forums or groups) are useful in connecting individuals to information, self-help strategies, health professionals, or peers, during periods of lockdown or restricted access.…”
Section: Discussionmentioning
confidence: 99%
“…Hovewer, due to the variation in study settings and inconsistencies in reporting, effectiveness is greatly dependent on the delivery format, targeted mental health problem and targeted purpose group. A study on digital mental health [36], synthesized evidence on digital health interventions targeting university students to evaluate their effectiveness. The results indicated that web-based online/computer delivered-interventions were effective or at least partially effective at decreasing depression, anxiety, stress and eating disorder symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Female students want communication that is more straightforward and contains more targeted and specific information, written in simple, clear language and requiring them to act (Sutton, 2017), like the communication present on social networks (Sheeran and Cummings, 2018). Yet, these social platforms are not specifically designated for academic sharing (Harith et al, 2022) and they do not provide a way to distinguish the educational context from the students' personal life (Waycott et al, 2010). This finding highlights the need for universities to promote and mentor the use of centralized information platforms for students dedicated exclusively to the academic context (Harith et al, 2022).…”
Section: Coping Strategies Used By the Female Students In The Academi...mentioning
confidence: 99%